2016
DOI: 10.1097/shk.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Platelets and Platelet-Derived Microparticles on Hypercoagulability Following Burn Injury

Abstract: An acute burn induced coagulopathy develops after scald injury, which evolves into a subacute, hypercoagulable state. Microparticles, specifically platelet-derived MPs (PMPs), have been suggested as possible contributors. We first developed a model of burn-induced coagulopathy and then sought to investigate the role of platelets and PMPs in coagulation after burn. We hypothesized that changes in circulating platelet and PMP populations after injury would contribute to the post-burn, hypercoagulable state. A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…In the present study we did not evaluate platelet-derived MVs, because our primary focus was to investigate the roles of MVs in the acute inflammatory response, rather than coagulopathy. Hypercoagulability is an important component of severe burns pathophysiology, and indeed a recent animal study using mice has reported acute increases in circulating pro-coagulant platelet-derived MVs following a scalding injury [23]. However, coagulopathy may not be yet present at patient admission as part of the acute trauma response [24, 25] and therefore temporally distinct from acute onset SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we did not evaluate platelet-derived MVs, because our primary focus was to investigate the roles of MVs in the acute inflammatory response, rather than coagulopathy. Hypercoagulability is an important component of severe burns pathophysiology, and indeed a recent animal study using mice has reported acute increases in circulating pro-coagulant platelet-derived MVs following a scalding injury [23]. However, coagulopathy may not be yet present at patient admission as part of the acute trauma response [24, 25] and therefore temporally distinct from acute onset SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that, in human serum, most EVs are P-EVs, although EVs can also be generated from white blood cells and cancer cells 15 - 17 . P-EVs have been found to participate in a variety of important biological and pathological processes via intracellular communication 18 , 19 , including clotting 20 , 21 , angiogenesis 22 , 23 , inflammation 24 , 25 , immunoregulation 3 , cellular prion protein transport 26 , and tumor progression 25 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies in humans and murine models of burn injuries describe an initial hypercoagulable state despite the presence of thrombocytopenia [6][7][8][9] . This nding suggests that systemic platelet activation, which likely precedes platelet consumption, plays a crucial role in mediating hypercoagulability as a result of burn injuries 7,10,11 . Although the exact mechanisms of increased platelet activation in these patients are unknown, endothelial stress and injury during in ammation may facilitate platelet rolling and activation, and subsequent platelet-immune cell interactions via toll-like receptors (TLR) fueling further in ammation [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 97%